Improvement of Health Status of Litsea monopetala using Plant Growth Promoting Rhizobacteria - Acharya, Amrita; Chakraborty, Usha; Chakraborty, Bishwanath (International Journal of Bio-resource and Stress Management, 2023)
Litsea monopetala (Roxb.) Pers. (Lauraceae) is one of the primary host plants of muga silk worm in Northeast India, with the local name Sualu. In muga sericulture, the muga silkworm Antherea assamensis, is fed on the leaves of Sualu, the primary host plant. A study was made to improve the quality and quantity of the leaves of the plant through the application of different plant growth promoting rhizobacteria (PGPR). Two isolates each of B. pumilus (BRHS/C1and BRHS/T82) and B. altitudinus (BRHS/P22 and BRHS/S73) and one isolate of Paenibacillus lentimorbus (TRS-5) were tested for their growth promoting activity in this plant. These were directly applied as foliar spray and also applied to the soil. Results were computed in terms of increase in plant height, leaf area index and compared with control sets. Among these, B. pumilus (BRHS/C1) was found to be more effective on growth and development of plants followed by B. pumilus (BRHS/T82), P. lentimorbus (TRS-5), B. altitudinus (BRHS/P22) whereas B. altitudinus (BRHS/S73) showed less effect. A significant increase in phenolics, total protein content as well as defense related enzymes such as peroxidase, phenylalanine ammonia-lyase, chitinase and β-1,3-glucanase were also observed following application of PGPR. In this present study B. pumilus (BRHS/C1) was found to be most effective in promoting over-all growth of Sualu plants which is a promising trait for utilizing such beneficial PGPR for effective plant growth-promotion that broadens the spectrum of use of beneficial microorganisms for sustainable crop management.